2017
DOI: 10.1590/1984-0462/;2017;35;1;00011
|View full text |Cite
|
Sign up to set email alerts
|

Análise Das Infecções De Sítio Cirúrgico Em Pacientes Pediátricos Após Cirurgia Ortopédica: Um Estudo Caso-Controle

Abstract: Objectives: To describe the rate of surgical site infections in children undergoing orthopedic surgery in centers of excellence and analyze the patients’ profiles. Methods: Medical records of pediatric patients undergoing orthopedic surgery in the Jamil Haddad National Institute of Traumatology and Orthopedics from January 2012 to December 2013 were analyzed and monitored for one year. Patients diagnosed with surgical site infection were matched with patients without infection by age, date of admission, field … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0
4

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 16 publications
0
4
0
4
Order By: Relevance
“…In a cross-sectional study, 20 obesity was, among other chronic diseases, a risk factor for the development of SSI in 9.5% of patients undergoing surgery. Another study published in 2017, 21 which aimed to assess risk factors for SSI, also showed a significant frequency of 21% of patients with obesity. In another cohort study with patients who underwent bariatric surgery, it was identified that there is a proportionality between the increase in the body mass index (BMI) range and the incidence of SSI cases.…”
Section: Assessment Of Intrinsic Risk Factors and Patient Characteristicsmentioning
confidence: 97%
See 1 more Smart Citation
“…In a cross-sectional study, 20 obesity was, among other chronic diseases, a risk factor for the development of SSI in 9.5% of patients undergoing surgery. Another study published in 2017, 21 which aimed to assess risk factors for SSI, also showed a significant frequency of 21% of patients with obesity. In another cohort study with patients who underwent bariatric surgery, it was identified that there is a proportionality between the increase in the body mass index (BMI) range and the incidence of SSI cases.…”
Section: Assessment Of Intrinsic Risk Factors and Patient Characteristicsmentioning
confidence: 97%
“…One of the selected articles pointed out the use of implants as one of the factors that predisposes to the occurrence of SSI, mainly related to the formation of biofilms on the implant surface, which can interfere with the patient's immunological defense and the effectiveness of antibiotic therapy. 21 In addition , the bacteria that make up biofilms have the possibility of sharing genetic materials through conjugation, a worrying factor in the hospital environment as it facilitates the exchange of bacterial resistance genes, reducing the antimicrobial alternatives for treating SSI. 26,27 Immunosuppressants are drugs that act by inhibiting cell division and decreasing the inflammatory process, they are indicated to prevent rejection of transplanted organs and to treat inflammatory diseases.…”
Section: Assessment Of Extrinsic Risk Factorsmentioning
confidence: 99%
“…Dessa forma, a literatura aponta que os principais fatores de risco para ISC em cirurgias ortopédicas são: a condição clínica do paciente 5,7 ; diabetes mellitus, obesidade, idade 6,[8][9] , internação pré-operatória prolongada 5,9 , antissepsia da pele; técnica de degermação e uso de Equipamentos de Proteção Individual (EPI's) pela equipe 7,10 e duração da cirurgia [8][9][10] .…”
Section: Introductionunclassified
“…Ë importante que se tenha um controle destas ISCs sendo um importante indicador de vigilância dos pacientes cirúrgicos tanto para a gestão quanto para a assistência. O acompanhamento sistemático da sua prevalência possibilita o planejamento de ações preventivas e a elaboração de estratégias de controle dessas infecções (CHAGAS et al, 2017).…”
Section: Introductionunclassified